Aplikasi Penilaian Kinerja Dosen pada Proses Belajar Mengajar Berbasis Web: Studi Pada STTI NIIT - HM. Anwar; Ari Santoso (KALBISCIENTIA Jurnal Sains dan Teknologi, 2023)
This article writes about making a lecturer performance questionnaire application which is made to make it easier to convey the aspirations of students to the maximum with access that can be done anywhere. Apart from being used as a means of aspiration for students, this application is also useful for monitoring lecturer performance, lecture material, and managing relevant data for admins. This application consists of one page for the user and one page for the admin. The user page only has questionnaire questions, while the admin page can manipulate data such as changing, adding, and deleting questions. On the admin page there is also a menu to view graphs and questionnaire results from users. The results of this application are very useful for improving the performance of the teaching and learning process at the STTI NIIT, Jakarta.